2013
DOI: 10.3390/molecules18033168
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Motion and Rearranged Molecular Shape of Heme in Myoglobin: Structural and Functional Consequences

Abstract: Myoglobin, a simple oxygen binding protein, was reconstituted with various types of synthetic hemes to manipulate the heme-globin interactions. From the paramagnetic NMR analysis, small heme was found to rotate rapidly about the iron-histidine bond upon. This is a novel and typical example for the fluctuation of protein. The dynamic NMR analysis indicated that the 360° rotational rate of a small heme was 1,400 s −1 at room temperature. The X-ray analyses revealed that the tertiary structure of globin containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Such electro-optical disparity between the two categories could be expounded in comparative cyclic voltammograms (CVs) as merged in Figure B. Pertaining to the well-known redox of FePPIX (curve a), one cathodic surge at E p1,c = −0.295 V (Table S1 in the Supporting Information) is accredited to the paralleled electroreduction from deoxygenated Fe III to Fe II in the d yz orbital (Scheme ) that donates electron to O 2 reduction reaction (ORR) . Other (quasi-)­reversibility is related to the electronic cycle about π* (or e g in Schoenflies symbol) of PPIX at −0.845 ( E p2,c )/–0.688 ( E p2,a ) V and −1.039 ( E p3,c )/–0.972 ( E p3,a ) V. , Concerning the electrochemical behavior of Hb FePPIX , all peak currents ( i p ) wane except a prominent bulge at E p1,c = −0.278 V (curve b), which stays closer to zero than curve a by 17 mV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such electro-optical disparity between the two categories could be expounded in comparative cyclic voltammograms (CVs) as merged in Figure B. Pertaining to the well-known redox of FePPIX (curve a), one cathodic surge at E p1,c = −0.295 V (Table S1 in the Supporting Information) is accredited to the paralleled electroreduction from deoxygenated Fe III to Fe II in the d yz orbital (Scheme ) that donates electron to O 2 reduction reaction (ORR) . Other (quasi-)­reversibility is related to the electronic cycle about π* (or e g in Schoenflies symbol) of PPIX at −0.845 ( E p2,c )/–0.688 ( E p2,a ) V and −1.039 ( E p3,c )/–0.972 ( E p3,a ) V. , Concerning the electrochemical behavior of Hb FePPIX , all peak currents ( i p ) wane except a prominent bulge at E p1,c = −0.278 V (curve b), which stays closer to zero than curve a by 17 mV.…”
Section: Resultsmentioning
confidence: 99%
“…Pertaining to the well-known redox of FePPIX (curve a), one cathodic surge at E p1,c = −0.295 V (Table S1 in the Supporting Information) is accredited to the paralleled electroreduction from deoxygenated Fe III to Fe II in the d yz orbital (Scheme 2) that donates electron to O 2 reduction reaction (ORR). 44 Other (quasi-)reversibility is related to the electronic cycle about π* (or e g in Schoenflies symbol) of PPIX at −0.845 (E p2,c )/−0.688 (E p2,a ) V and −1.039 (E p3,c )/−0.972 (E p3,a ) V. 39,45 9,46 As for apo-Hb, it can turn into apo-oxyhemoglobin (apo-oxyHb) but lost its electrocatalytic ability, which puts ORR off until −0.665 V (curve c), no better than a pretreated bare glassy carbon. Getting down to the extrinsic ZnPPIX, it also responds to the dissolved O 2 that resembles the parallel catalytic wave in curve a (curve d) but differs dramatically in the hopping path as already been elaborated on elsewhere.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…HO-1 is powerfully cytoprotective through increased enzymatic degradation of heme into three bioactive molecules: carbon monoxide (CO), iron, and biliverdin (Otterbein et al, 2003). Among all known mechanisms of cytoprotection, the heme degradation pathway is the only catalytic process that allows removal of heme released from damaged cells and tissues, especially skeletal muscle, in which there is an enormous concentration confined within myoglobin (Neya, 2013). We have previously reported that HO-1 and its product CO are potently protective in muscular dystrophy (Chan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The heme orientational disorder demonstrated that the molecular recognition upon insertion of the heme into the Mb heme pocket is not as strict as that for the formation of usual enzyme–substrate complexes . Furthermore, broad molecular recognition of the Mb heme pocket is clearly reflected in its capacity to accommodate a variety of guest molecules ranging from chemically modified heme complexes ,,, and analogues , to metal complexes with salophen ligands . Characterization of the molecular recognition of the Mb heme pocket is a problem of particular importance for elucidating the heme-protein interaction and thus crucial for functional control of the protein.…”
mentioning
confidence: 99%